Uighurs of Kazakhstan: historical destiny and its poetry (Journal of Oriental Studies, 2018)
The article deals with the movement of Uighurs from their historical homeland to Kazakh lands, tothe Chinese empire or to the murders of the Russian Empire, violence and poetry of the great destiny ofthe Uighur people. The works of Uighur diaspora poets, who are living in independent Kazakhstan, arecriticized for their lack of respect for historical attitudes